Stigmatisation and discrimination of people living with HIV and AIDS at Elim in Vhembe District : a jungian phenomenological study - Nkuna, Olivia Khensani (My University, 2016)
Exploring the lived experiences of People Living with HIV/AIDS in relation to stigma and discrimination was the purpose of this qualitative research underpinned by Jungian Phenomenology. The study was qualitative in nature with a non-probability sample of fifteen participants aged from twenty tree to sixty four years. The setting was a rural and the research took place at a designated HIV/AIDS clinic in Limpopo. Semi-structured interviews, in the vernacular, were constructed so that the in-depth, lived experience of the participants relating to stigmatisation and discrimination could be ascertained. The participants’ responses were organised through the application of the Jungian metaphors and presented as themes which were presented in English. The archetypes of the Self, Shadow and Persona were highlighted as dominant metaphors with the Animus playing an important. These were followed by archetypes which represented more marginal roles in the participants’ personality development namely, the Anima, Hero, Caregiver, Innocent and Orphan. Everyone has the desire to develop a well-rounded socially acceptable and fulfilling personality, whose development process is accompanied by the generation and maturation of various archetypal traits. Once this is achieved, the process of personal individuation is completed and an individual is able to experience their true Self and live a fulfilling and authentic (honest) life. HIV infection and HIV related stigma generate archetypal traits which tend to impede the personality development of individuals. As a result they were not able to merge their personality development into an integrated unit and emerge as spiritual and deep-thinking beings.
Thesis (Ph. D. (Psychology)) -- University of Limpopo, 2016.
Keywords: HIV/AIDS; AIDS patients; HIV (Viruses) -- South Africa -- Limpopo; AIDS (Disease) -- South Africa -- Limpopo; HIV-positive persons -- South Africa -- Limpopo; AIDS (Disease) -- Patients -- South Africa -- Limpopo